The production of managerial knowledge and organizational theory : new aproaches to writing, producing and consuming theory - Zilber, Tammar B.; Amis, John M.; Mair, Johanna (Bingley, U.K. : Emerald Publishing Limited, 2019)
As organizational scholars, we are accustomed to using theoretical lenses to understand organizational practices and outcomes. That is, we conceptualize what people do, feel and think in their everyday organizational interactions through the use of theoretical language and models to uncover individual and/or social antecedents and outcomes. We tend to ignore, however, how our own day-to-day work as scholars - doing research - is subjected to the same pressures, affected by similar factors, and should be accounted for through similar modes of analyses. We treat our studies and theories as solid anchor points and as objective truths rather than as constructions embedded within individual, organizational, field and societal contexts.This volume is a must read for all researchers interested in understanding our own craft. Building on established traditions in the sociology of knowledge, we direct a reflective and critical gaze towards the structures, practices and meaning systems that ground and shape how we produce and consume managerial knowledge and organization theory. The volume includes both empirically-based papers and reflective essays that explore theoretical concepts and analytical reasoning to explain, critique and advance the ways in which we write about, produce, and consume theory.
Prelims -- Introduction Dismantling the master's house using the master's tools: on the sociology of organizational knowledge -- Chapter 1: The problem of de-contextualization in organization and management research -- Chapter 2: Pragmatism in organizations: ambivalence and limits -- Chapter 3: Reframing rigor as reasoning: challenging technocratic conceptions of rigor in management research -- Chapter 4: Knowledge production and consumption in the digital era: the emergence of altmetrics and open access publishing in management studies -- Chapter 5: Peer review and the production of scholarly knowledge: automated textual analysis of manuscripts revised for publication in Administrative Science Quarterly -- Chapter 6: The (re?)emergence of new ideas in the field of organizational studies -- Chapter 7: A discourse perspective on creating organizational knowledge: the case of strategizing -- Chapter 8: When fieldwork hurts: on the lived experience of conducting research in unsettling contexts -- Chapter 9: Visual artefacts as tools for analysis and theorizing -- Chapter 10: Presenting findings from qualitative research: one size does not fit all! -- Chapter 11: For social reflexivity in organization and management theory -- Chapter 12: Through the looking glass': on phantasmal tales, distortions and reflexivity in organizational scholarship -- Chapter 13: When research and personal lifeworlds collide -- Index.
Includes index.
Print version record
Keywords: Management science; Industrial organization; Social Science -- Sociology -- General; Organizational theory & behaviour